2021
DOI: 10.3390/children8030236
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Black/African American and Hispanic Parents and Children Living in Under-Resourced Communities Regarding Factors That Influence Food Choices and Decisions: A Qualitative Investigation

Abstract: Families living in under-resourced communities are at risk of obesity and obesity-related chronic diseases. To develop effective interventions, it is important to identify parent and child perspectives of factors that influence food-related choices and decisions. This paper reports qualitative findings from a larger mixed method study investigating this topic. Hybrid thematic analysis was used to code and analyze the interviews. Family-generated photographs of factors influencing food choices were discussed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
(60 reference statements)
1
5
0
Order By: Relevance
“…However, the majority of the households represented had an individual with at least a college degree. The fact that education status did not necessarily predict the socioeconomic diversity of the sample is consistent with other studies in minority populations that have shown that income disparities can persist despite educational status [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the majority of the households represented had an individual with at least a college degree. The fact that education status did not necessarily predict the socioeconomic diversity of the sample is consistent with other studies in minority populations that have shown that income disparities can persist despite educational status [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…Parents’ perspectives on strategies for healthy dietary choice promotion for children have been well studied [ 37 , 38 ]. However, less attention has been given to minority parents’ perceptions regarding ways to help children practice healthy lifestyle behaviors [ 29 , 39 , 40 ]. Furthermore, community-based participatory research, while it can be difficult to evaluate its effect on participation, shows that participant engagement strengthens the program’s ability to equitably distribute the benefits of a program or overcome barriers such as in our socioeconomically diverse parent population [ 21 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Families provided written informed consent prior to participation in the study. A more detailed description of the recruitment procedures is reported elsewhere [12].…”
Section: Recruitmentmentioning
confidence: 99%
“…The home food environment [8], family meals [9], food preferences [10], and household income [11] contribute to children's dietary behaviors. Children can also influence food behaviors in both themselves [9] and their family [12]. The diet quality of children in the United States is below the national dietary recommendations [13].…”
Section: Introductionmentioning
confidence: 99%
“…Many factors influence child dietary intake [13][14][15], the most important of which need to be taken into consideration when making personalized dietary change prescriptions. High among these influences, especially for younger children, is parents [16].…”
Section: Introductionmentioning
confidence: 99%